Gavriil Sevir vs Antonio Possevino in the controversy around “Moscovia” - Alexey Yastrebov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article aims to show the existence of stable ties between the Metropolitanate of Philadelphia of the Patriarchate of Constantinople and the Russian Orthodox Church at the end of the 16th century. Last but not least, the establishment of these contacts was facilitated by the active position of the ruling bishop of the metropolis. In addition, texts belonging to the pen of two theologians and clergymen who were directly related to Russia and the Russian Church — Jesuit Antonio Possevino and Metropolitan Gavriil Sevir of Philadelphia — are being introduced into scientifi c circulation. Both of them, Catholic and Orthodox, each from their own point of view, appreciated the faith and rituals of the Orthodox Church. The fi nal chapter of the treatise “Muscovy” by A. Possevino informs us about what views he had on religion in the Moscow state, representing a certain list of doctrinal “mistakes” of the Russians, which Metropolitan Gabriel chose to defend. His letter, being an apology for the whole of Orthodoxy, primarily defends the Russian Church, against which the “capita” of the Jesuit were directed. Finally, the latter’s answer is interesting not so much from the theological point of view. It, like Gabriel’s message, is valuable as an illustrative example of principled but respectful discussion. Of course, this does not exclude the fact that each tried to achieve his goal and to some extent dull the opponent’s vigilance. The metropolitan’s genuine attitude to Possevino is demonstrated, for example, by the remark published below in the preface to the later edition of one of his works. All this makes the documents, first published in Russian, important sources for the history of the Roman Catholic, Russian and Greek Orthodox Churches.